The Relationship of Social Support with The Level of Independence for People with Mental Disorders (ODGJ) in Menur Mental Hospital (RSJ) Surabaya - Widiyawati, Wiwik (Poltekkes Kemenkes Palu, 2023)
Mental health is one of the things that is currently becoming an international issue discussed in the SDGs (Sustainable Development Goals). The healing process for ODGJ is carried out by carrying out mental rehabilitation. The intense support that people with mental disorders receive from outside themselves sometimes goes unnoticed, whether it comes from family, friends or health workers. The aimed to study and analyse the relationship between support from family, friends, and health workers on the level of independence in ODGJ. This research is a type of observational analytical research with a cross-sectional approach. Data collection was carried out using a questionnaire. The data in this study were analysed univariately using frequency distribution tables and bivariate using cross tables and the chi-square statistical test with significance α=0.05 using SPSS. The research results show that there is a relationship between support and the level of independence of ODGJ (p= 0.012), there is a relationship between friend support and the level of independence of ODGJ (p= 0.027), and there is a relationship between support from health workers and the level of independence for ODGJ (p= 0.001).